Value and sustainability in technology-enabled care services: a case study from north-east England. Issue 4 (19th May 2022) - Bhattacharya, Suman; Wainwright, David; Whalley, Jason
IMPACT: A critical barrier to the large-scale adoption of technology-enabled care services (TECS) remains a lack of evidence around their business cases that would create sufficient value for the stakeholders involved. Drawing on a case study of telecare service delivery, involving public funding and institutions in north east England, the authors highlight the opportunities that technology provides, as well as a series of challenges that need to be addressed. The findings will be particularly helpful for telecare stakeholders, shaping how services are provided. ABSTRACT Technology-enabled care services (TECS) are primarily provided in the UK as a public service, using public funds and national systems of health and care. The delivery of such services, however, is increasingly market orientated and subject to many challenges. The authors draw on the literature and case study evidence, to explore the value propositions and value co-creation within TECS, highlighting the challenges and obstacles, as well as possible ways forward.